2018
DOI: 10.1111/are.13792
|View full text |Cite
|
Sign up to set email alerts
|

Dietary krill meal inclusion contributes to better growth performance of gilthead seabream juveniles

Abstract: There is a need to find sustainable alternatives to fishmeal (FM) and fish oil (FO) in feed formulations to support the continued growth of aquaculture. FM is mostly produced from mass-caught pelagic species, but the production has been relatively constant for several decades. The aim of this study was to investigate the potential of dietary krill meal (KM) inclusion as a sustainable alternative to FM. In view of that, a feeding trial with gilthead seabream juveniles was conducted to evaluate whether dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…According to the results of the present study, partial inclusion of KM seemed to improve the growth performance and feed utilization of olive flounder confirming earlier investigations on dietary KM supplementation for other fish species (Gaber, 2005;Hansen et al, 2011;Olsen et al, 2006;Saleh et al, 2018;Suontama, Karlsen, et al, 2007;Suontama, Kiessling, Melle, Waagbø, & Olsen, 2007;Tibbetts et al, 2011;Wei et al, 2019). The improved FIs of the KM3, KM6 and KM9 groups compared to the LFM group may be a result of feed attractant properties of KM, which led to higher appetite as described by Kolkovski, Czesny, and Dabrowski, (2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the results of the present study, partial inclusion of KM seemed to improve the growth performance and feed utilization of olive flounder confirming earlier investigations on dietary KM supplementation for other fish species (Gaber, 2005;Hansen et al, 2011;Olsen et al, 2006;Saleh et al, 2018;Suontama, Karlsen, et al, 2007;Suontama, Kiessling, Melle, Waagbø, & Olsen, 2007;Tibbetts et al, 2011;Wei et al, 2019). The improved FIs of the KM3, KM6 and KM9 groups compared to the LFM group may be a result of feed attractant properties of KM, which led to higher appetite as described by Kolkovski, Czesny, and Dabrowski, (2000).…”
Section: Discussionsupporting
confidence: 89%
“…Tibbetts, Olsen, and Lall, (2011) reported that moderate FM replacement (25%-50%) with freeze-dried KM was able to obtain significant improvements in FI and growth performance in Atlantic cod (Gadus morhua) and Atlantic halibut. In juvenile gilthead seabream (Sparus aurata), 9% KM inclusion in diets performed significantly better in growth and feed conversion ratio (FCR; Saleh et al, 2018).…”
mentioning
confidence: 99%
“…The use of animal meal such as krill or meat and bone meals for fishmeal replacement was efficient in improving fish growth performance and FCR but none resulted in a FIFO index below 1. In fact, in the case of diets with krill meal, this index was even higher than in the original diet (1.3 vs. 1.2), since both fish- and krill-meal in the experimental diet were included in the calculation of the fish-in value, which was 25% as compared to only 20% in the control diet with fishmeal alone 52 . A FIFO index below 1, as was measured in the experimental diets tested in the current study (0.5–0.9), was obtained only in studies in which fishmeal was totally removed from diet, with the sole exception of one diet using a plant protein mixture 7 .…”
Section: Discussionmentioning
confidence: 87%
“…Various stimulants and attractants are widely applied to contribute this feature to feeds, particularly in scientific studies where vegetable protein sources are used as alternatives in fish feeds (Al‐Souti et al., 2019). For instance, it is stated that krill meal is used as a chemoattractant in shrimp diets (Saleh et al., 2018), fish silage in white pacific shrimp diets, whereas amino acids such as alanine, hydroxyproline, phenylalanine, leucine, partially proline and nucleotides are considered as chemoattractants for rainbow trout (Kohbara & Caprio, 2001; Marui et al., 1983). In this study, it is presumed that the reason for fish not to prefer snail meal‐based diets as compared to the control diet depends upon a different reason, considering all the amino acids that are recognized to be attractive for rainbow trout were present in the feed above the minimum requirements for the fish.…”
Section: Discussionmentioning
confidence: 99%